A multicenter, open‐label, single‐arm study of anamorelin (ONO‐7643) in patients with cancer cachexia and low body mass index. Issue 10 (23rd February 2022) - Naito, Tateaki; Uchino, Junji; Kojima, Toru; Matano, Yutaka; Minato, Koichi; Tanaka, Kentaro; Mizukami, Takuro; Atagi, Shinji; Higashiguchi, Takashi; Muro, Kei; Takayama, Koichi; Furuse, Junji; et al.
Abstract : Background: Cancer cachexia is a syndrome characterized by anorexia and decreased body weight. This study evaluated the efficacy and safety of anamorelin, an orally active, selective ghrelin receptor agonist, in patients with cancer cachexia and a low body mass index (BMI). Methods: This multicenter, open‐label, single‐arm study enrolled Japanese patients with non–small cell lung cancer or gastrointestinal cancer with cancer cachexia (BMI < 20 kg/m 2, involuntary weight loss > 2% in the last 6 months, and anorexia). Patients were administered 100 mg of anamorelin once daily for up to 24 weeks. The primary end point was a composite clinical response (CCR) at 9 weeks, which was defined as an increase in body weight of ≥5% from the baseline, an increase of ≥2 points in the score of the 5‐item Anorexia Symptom Scale of the Functional Assessment of Anorexia/Cachexia Therapy, and being alive. Results: One hundred two patients were eligible and enrolled. The means and standard deviations for age and BMI were 71.0 ± 8.2 years and 17.47 ± 1.48 kg/m 2, respectively. The CCR rate at 9 weeks was 25.9% (95% confidence interval [CI], 18.3%‐35.3%), which met the primary end point with a lower 95% CI exceeding the prespecified minimum of 8%. Improvements in body weight and anorexia were durable and were accompanied by improvements in patients' global impression of change for appetite/eating‐related symptoms and overall condition. Adverse drug reactions occurred in 37 of 101 treated patients (36.6%), with the most common being glycosylated hemoglobin increases, constipation, and peripheral edema. Conclusions: Anamorelin improved body weight and anorexia‐related symptoms in patients with cancer cachexia and a low BMI with durable efficacy and favorable safety and tolerability. Lay Summary: Anamorelin is a drug that stimulates appetite and promotes weight gain. This clinical trial was aimed at determining its efficacy and safety in Japanese cancer patients with a low body mass index and cachexia, a syndrome associated with anorexia and weight loss. Anamorelin was found to improve body weight and anorexia‐related symptoms in these patients, and these effects were durable for up to 24 weeks. Moreover, anamorelin was generally well tolerated. These findings suggest that anamorelin is a valuable treatment option for patients with cancer cachexia and a low body mass index. Abstract : This single‐arm trial is aimed at investigating the efficacy and safety of anamorelin in Japanese patients with cancer cachexia and a low body mass index. Anamorelin improves body weight and anorexia‐related symptoms with durable efficacy and favorable safety and tolerability.